Hematopoietic stem cell transplantation does not increase the risk of infection‐related complications for pediatric patients with Hodgkin and non‐Hodgkin lymphomas: A multicenter nationwide study. Issue 4 (23rd April 2020) - Zając‐Spychała, O.; Wachowiak, J.; Czyżewski, K.; Dziedzic, M.; Wysocki, M.; Zalas‐Więcek, P.; Szmydki‐Baran, A.; Hutnik, Ł.; Matysiak, M.; Małas, Z.; Badowska, W.; Gryniewicz–Kwiatkowska, O.; et al.
Abstract: Background: Hodgkin (HL) and non‐Hodgkin lymphoma (NHL) represent a spectrum of lymphoid malignancies that are often curable with currently applied treatment regimens; however, 15%‐30% of lymphoma patients still suffer from relapsed or refractory (rel/ref) disease. Although hematopoietic stem cell transplantation (HSCT) improves outcomes of second‐line therapy for lymphoma in childhood, the complication rates in this group of patients, especially infectious complications (IC), remain unclear. Objective: The aim of this population‐based cohort study was a retrospective analysis of incidence, epidemiology and profile of bacterial infections (BI), invasive fungal disease (IFD), and viral infections (VI) in primary or rel/ref lymphoma patients, both HL and NHL. Patients and methods: We subdivided lymphoma patients into three groups: patients with primary conventional chemotherapy/radiotherapy regimens (group A), patients with rel/ref lymphoma treated with second‐line chemotherapy (group B), and rel/ref lymphoma patients who underwent HSCT (group C). The medical records of the patients were biannually reported by each pediatric oncology center, and the data were analyzed centrally. Results: Within 637 patients with primary lymphoma, at least one IC was diagnosed in 255 (40.0%), among 52 patients with rel/ref lymphoma 24 (46.2%) ICs were observed, and in transplanted group, 28 (57.1%) out of 49 children were diagnosed with IC ( P = .151). The distribution of etiology of IC differed between the patient groups (A, B, C), with a predominance of BI in group A (85.6% vs 72.0% and 47.9%, respectively), VI in group C (9% and 16.0% vs 46.6%, respectively), and IFD in group B (5.4% vs 12.0% vs 5.5%, respectively). Overall, 500 (68.0%) episodes of bacterial IC were diagnosed in the entire group. Apart from HL patients treated with chemotherapy, in all the other subgroups of patients Gram‐positives were predominant. The rate of multidrug‐resistant bacteria was high, especially for Gram‐negatives (41.1% in group A, 62.5% in group B, and 84.6% in group C). The infection‐related mortality was comparable for each group. Conclusions: The incidence of IC was comparable during first‐ and second‐line chemotherapy and after HSCT, but their profile was different for primary or re/ref lymphoma and depended on the type of therapy.